East Asian Mothers in Britain An Intersectional Exploration of Motherhood and Employment - Lim, Hyun-Joo (Palgrave Macmillan Studies in Family and Intimate Life, 2018)
How do Chinese, Japanese and Korean mothers in Britain make sense of their motherhood and employment? What are the intersecting factors that shape these women's identities, experiences and stories? Contributing further to the continuing discourse and development of intersectionality, this book examines East Asian migrant women's stories of motherhood, employment and gender relations by deploying interlocking categories that go beyond the meta axes of race, gender and class, including factors such as husbands' ethnicities and the locality of their settlement. Through this, Lim argues for more detailed and context specific analytical categories of intersectionality, enabling a more nuanced understanding of migrant women's stories and identities. East Asian Mothers in Britain will appeal to students and scholars across a range of disciplines and with an interest in identity, gender, ethnicity, class, migration and intersectionality.